2020
DOI: 10.1038/s41467-020-19944-x
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light photoredox-catalyzed C–O bond cleavage of diaryl ethers by acridinium photocatalysts at room temperature

Abstract: Cleavage of C–O bonds in lignin can afford the renewable aryl sources for fine chemicals. However, the high bond energies of these C–O bonds, especially the 4-O-5-type diaryl ether C–O bonds (~314 kJ/mol) make the cleavage very challenging. Here, we report visible-light photoredox-catalyzed C–O bond cleavage of diaryl ethers by an acidolysis with an aryl carboxylic acid and a following one-pot hydrolysis. Two molecules of phenols are obtained from one molecule of diaryl ether at room temperature. The aryl carb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Inspired by the pioneering work of Fukuzumi and his co-workers on the oxidation of benzyl alcohol using 9-phenyl-10-methylacridium as the OPC, and by the recent C–O bond cleavage of diaryl ethers by acridinium photocatalysts, the fragmentation of C β O–Ar bond induced by acridinium-based OPCs was investigated. The choice for 2-(2-methoxyphenoxy)-1-phenylethan-1-ol ( 31 ) as a model substrate was made because its phenolic unit is enriched by a methoxy substituent thus facilitating its single-electron oxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Inspired by the pioneering work of Fukuzumi and his co-workers on the oxidation of benzyl alcohol using 9-phenyl-10-methylacridium as the OPC, and by the recent C–O bond cleavage of diaryl ethers by acridinium photocatalysts, the fragmentation of C β O–Ar bond induced by acridinium-based OPCs was investigated. The choice for 2-(2-methoxyphenoxy)-1-phenylethan-1-ol ( 31 ) as a model substrate was made because its phenolic unit is enriched by a methoxy substituent thus facilitating its single-electron oxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 19 Recently, the degradation of DPE was realized by Li et al through esterification under light with an acridinium photocatalyst with two molecules of phenols obtained via the following hydrolysis. 20 Meanwhile, the cleavage of C–C 21 and β-O-4 22 , 23 linkages of lignin were achieved with the development of photocatalysis. 24 27 …”
mentioning
confidence: 99%
“…19 Recently, the degradation of DPE was realized by Li et al through esterification under light with an acridinium photocatalyst with two molecules of phenols obtained via the following hydrolysis. 20 Based on our previous study on uranyl species, 28 the ligandto-metal charge transfer (LMCT) mode and superior oxidative ability [E ox = +2.60 V vs SCE] 29−32 supply great potential for DPE activation [E ox = +1.88 V vs SCE]. 33 Herein, the photocatalyzed hydrolysis of diaryl ethers was established to afford two kinds of phenols via uranyl catalysis with visible light stimulation at room temperature and normal pressure (Scheme 1d).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoredox catalysis holds great promise in sustainable organic synthesis and has been attracting broad interests in the past decade. Key to the success of this chemistry and its further development resides in the development of catalysts with adjustable physical, photophysical, and electrochemical properties. Acridinium dye 1 (Scheme A), first introduced by Fukuzumi, , has become one of the most popular organic photocatalysts because of its favorable excited-state properties such as a high reduction potential ( E* red = 2.06 V vs standard calomel electrode (SCE)) and good lifetime (τ = 6 ns). ,, Recent work by the Nicewicz group has shown that a modification of the acridinium core with alkyl groups leads to more robust catalysts such as 2 that bear tert -butyl ( t Bu) groups at positions 3 and 6 (Scheme B). While the acridinium dye 2 can be prepared by adding an aryl Grignard reagent to a t Bu-substituted acridone or the reaction of a doubly lithiated biarylether with an ester (Scheme B), the synthesis of acridinium dyes bearing other alkyl groups on the core remained rather challenging and underexplored.…”
mentioning
confidence: 99%